Comparison of the physiological responses and time-motion characteristics of young soccer players in small-sided games: The effect of goalkeeper - Köklü, Y.; Sert, Ö.; Alemdaroglu, U.; Arslan, Y. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to investigate the effect of "with goalkeeper" (SSGwith) and "without goalkeeper" (SSGwithout) conditions on players' physiological responses and time-motion characteristics in small-sided games. Sixteen young soccer players (age: 16.5 ± 1.5 years; height: 175.5 ± 5.2 cm; body mass: 63.0 ± 6.9 kg; training experience: 6.3 ± 1.3 years) participated in 2 different 2-a-side, 3-a-side, and 4-a-side games: SSGwith and SSGwithout. The players underwent anthropometric measurements (height and body mass) followed by the Yo-Yo intermittent recovery test (level 1). Then they played 2-a-side, 3-a-side, and 4-a-side SSGwith and SSGwithout soccer-specific SSGs in random order at 2-day intervals. Heart rate (HR) responses and distance covered in different speed zones (walking [WLK, 0-6.9 km/h], low-intensity running [LIR, 7.0-12.9 km/h], moderate-intensity running [MIR, 13.0-17.9 km/h], and high-intensity running [HIR, >18 km/h]) were measured during the SSGs, whereas the rating of perceived exertion (RPE) and blood lactate (La-) were determined at the end of the last bout of each SSG. During the SSGwithout players showed higher %HR, La-, and RPE (p = 0.05), greater distance covered in LIR, MIR, HIR, and total distance (p = 0.05) compared with the SSGwith during the 2-a-side, 3-a-side, and 4-a-side games. The results of this study suggest that both SSGwith and SSGwithout could be used for the physiological adaptations required for soccer-specific aerobic endurance. However, if coaches want both higher physiological responses and greater distance covered in the intensity running zone from their teams, SSGwithout should be organized. In addition, this study also suggests that smaller format games (i.e., 2-a-side) may promote some anaerobic adaptations for youth soccer players.